Photodegradation of the pure and formulated scoparone in liquid solutions kinetics and mechanism - Luo, Jinxiang (Environmental technology, 2024)
Scoparone (hereafter SPR) is a prominent candidate of plant-derived acaricide. The photodegradation of the pure SPR was first investigated under different light sources, initial concentrations, pH values, temperatures, organic solvents, aqueous media, and the photolytic characteristics of its formulation in pure water were also studied. The photodegradation rates of pure SPR under different light sources showed the following sequence: 28 W ultraviolet lamp (0.3045 h-1) > 500 W xenon lamp (0.1094 h-1) > 300 W xenon lamp (0.0312 h-1). Under the irradiation of 500 W xenon lamp, the lower initial SPR concentrations, higher pH value, and higher temperatures increased the photodegradation rates of SPR, especially, when the temperature increased higher than 35℃, the degradation rate of SPR increased slowly and maintained at a stable level, the pH and temperatures had small effects on the photodegradation of SPR. The photodegradation rates of pure SPR in organic decreased comparing to in aqueous media. The removal efficiency of 98% SPR technical material (TC) was higher than 5% SPR emulsifiable concentrate (EC) in pure water, indicating that the components present in formulated SPR greatly affected the photodegradation kinetics. Detecting the photoproducts by HPLC/ESI-MS indicated that three main types of reaction including photorearrangement, photohydrolysis, and photooxidation occurred in the photodegradation of SPR at aqueous solution. These results will be helpful for the rational use of SPR and provide a scientific reference for environmental risk evaluation of SPR